FORMULA MAKANAN GLIKEMIK TINGGI UNTUK ANAK GIZI KURANG - Uken S. Soetrisno; Rossi R. Apriyantono; Maryanto Maryanto; Agus Drajat (Persagi, 2001)
High Glycaemic Food Formula For Under Nourished Children.Background: The reported prevalence of undernounshed children is highly increase since economic crisis. Six months food intervention based on skim milk only improved 65% of the undernourished children. Since gastrointestinal tract of such childrents incapable of digesting high molecular weight of carbohydrate and protein, there is a need to develop an easily digested food formula which has high glycaemic index.Objective: to produce high glycaemic index formula using dextrinized carbohydrate and fermented skim milk that is easily digested for undernourished children.Method: Two groups of subjects, each consists of 34 and 33 undernourished children were given either high glycaemic index formula (test group) or skim milk formula (control group) for 4 months. The food formula compliance, anthropometric measurement, blood and fecal component were analyzed.Results: There were increase in body weight of test group even though not changing their nutritional status based on Z-score. The blood and fecal component data indicated that the high glycaemic formula can be digested well by the undernourished children.Keywords: high glycaemic formula, undernourished